A Conceptual Model of Sufi-Based Sustainable Islamic Education within the Framework of the Sustainable Development Goals - Harto, Jemmy; Ali, Mufti (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
This study explores the relevance of Sufism to the framework of sustainable development, particularly within the context of Islamic education in Indonesia. It departs from the growing recognition that spirituality is often neglected in modern development paradigms and proposes an integrative Sufi-based approach as both an epistemological and practical foundation for sustainable education. Using a qualitative descriptive method through literature analysis and thematic interpretation of 22 open-access scholarly sources, this research identifies four essential Sufi values tazkiyah al-nafs (self-purification), tawāzun (balance), ihsān (excellence in action), and rahmah (universal compassion). These values demonstrate direct alignment with SDG 4 (quality education), SDG 13 (climate action), and SDG 16 (peace, justice, and strong institutions). Findings reveal that integrating Sufi values into Islamic education strengthens character formation, enhances ecological awareness, and fosters a culture of peace. Theoretically, this study extends the framework of Education for Sustainable Development (ESD) into a Spiritual Sustainability Education (SSE) paradigm, while practically offering a transformative model of Islamic education that unites faith, knowledge, and social responsibility as the moral foundation of sustainable development.